2016
DOI: 10.1021/acs.biochem.5b01362
|View full text |Cite
|
Sign up to set email alerts
|

The Disulfide Bonds within BST-2 Enhance Tensile Strength during Viral Tethering

Abstract: Human BST-2/tetherin is a host factor that inhibits the release of enveloped viruses, including HIV-1, HIV-2, and SIV, from the cell surface by tethering viruses to the host cell membrane. BST-2 has an α-helical ectodomain that forms disulfide-linked dimers between two monomers forming a coiled coil. The ectodomain contains three cysteine residues that can participate in disulfide bond formation and are critical for viral tethering. The role of the disulfides in viral tethering is unknown but proposed to be fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 42 publications
14
24
0
Order By: Relevance
“…Therefore, we simulated the transition from the membrane bound to the host cell-viral particle bridging forms. In a previous study, we showed that a steered molecular dynamics simulation pulling the termini of the BST-2 ectodomain to mimic viral tethering correlated well with biochemical experiments 13 . Therefore, we turned to steered molecular dynamics to simulate the conformational changes BST-2 during the transition to the bridging form using our model of the membrane bound, full-length BST-2.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…Therefore, we simulated the transition from the membrane bound to the host cell-viral particle bridging forms. In a previous study, we showed that a steered molecular dynamics simulation pulling the termini of the BST-2 ectodomain to mimic viral tethering correlated well with biochemical experiments 13 . Therefore, we turned to steered molecular dynamics to simulate the conformational changes BST-2 during the transition to the bridging form using our model of the membrane bound, full-length BST-2.…”
Section: Resultssupporting
confidence: 55%
“…For comparison, the only other BST-2 homolog with a structure is the mouse homolog so we aligned the crystals structures of the human and murine homologs (data not shown) 8,6 . We did not observe any gaps in the murine coil and note that melting temperature for the ectodomain of the murine BST-2 is higher than the value for the human homolog 8,13 . These data suggest that the mouse homolog has a more rigid dimer interface which might alter the structure of the ectodomain during the transition from membrane to bridging position.…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations